2015
DOI: 10.1007/s00590-015-1679-1
|View full text |Cite
|
Sign up to set email alerts
|

Does warming up improve surgical outcome in total hip arthroplasty?

Abstract: Warming up prior to performing surgery does not make a difference for primary THA when performed by an experienced surgeon. However, these results may not reflect its effect on procedures that require fine motor skills or done by an orthopedic trainee or less experienced surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
(20 reference statements)
1
6
0
Order By: Relevance
“…Our results differ from those of several randomised controlled trials on mental imagery in postgraduate education. Studies that involved surgical trainees’ ‘warming up’ with mental imagery16 17 described significantly improved performance with a warm-up before laparoscopic surgery. However, when considering the effects of warm-up on the different aspects of psychomotor performance, Paschold et al 27 found that these were affected by the nature of the warm-up, the type of surgery and the expertise of the surgeon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results differ from those of several randomised controlled trials on mental imagery in postgraduate education. Studies that involved surgical trainees’ ‘warming up’ with mental imagery16 17 described significantly improved performance with a warm-up before laparoscopic surgery. However, when considering the effects of warm-up on the different aspects of psychomotor performance, Paschold et al 27 found that these were affected by the nature of the warm-up, the type of surgery and the expertise of the surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated mental imagery in postgraduate settings,16–19 but only one small study used it during intravenous cannulation performed by undergraduate students 20. Mental imagery, due to its simplicity, could facilitate learning and skill maintenance in undergraduate medical student curricula, and release educators from the physical and temporal presence of bedside teaching.…”
Section: Introductionmentioning
confidence: 99%
“…Greater hand smoothness of movement (p < 0.03) 14 Smoothness of instruments (p < 0.05) 14 demonstrated, with rates of orthopaedic postoperative infections thought to be associated with case order, potentially secondary to inadequate cleaning interoperatively. 41 While most studies have found second and subsequent cases have shorter operative times, in comparison to the primary case of the day, 39,42 Makhdom et al 43 found that second and subsequent cases were significantly slower than the first case of the day. Lavelle et al 42 found that patient on second and subsequent cases on the operating list had shorter operative times, and hospital lengths of stay.…”
Section: Psychomotor Testingmentioning
confidence: 99%
“…They concluded that "warming up" may have beneficial outcomes as indicated by the finding that the conventional training group developed outcomes similar to that of the interventional arm with more exposure. Makhdom et al 62 investigated this concept by comparing the first patient's outcome with the outcomes of subsequent patients on the operating list, and noted no significant difference in outcomes between first and subsequent total hip arthroplasties on the theatre list.…”
Section: Impact Of Time On Simulation On Clinical Acumenmentioning
confidence: 99%